2020
DOI: 10.7150/ijbs.33787
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin induces cell cycle arrest, apoptosis and autophagy through ROS/JNK signaling pathway in human osteosarcoma

Abstract: Metformin, an ancient drug commonly used for treating type II diabetes, has been associated to anti-cancer capacity in a variety of developing cancers, though the mechanism remains elusive. Here, we aimed to examine the inhibitory effect of metformin in osteosarcoma. Herein, we demonstrated that metformin treatment blocked proliferation progression by causing accumulation of G2/M phase in U2OS and 143B cells. Furthermore, metformin treatment triggered programmed cell death process in osteosarcoma cell lines. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 50 publications
7
82
0
1
Order By: Relevance
“…The results of the present study indicated that metformin significantly reduced human cervical cancer cell viability (CaSki, C33A and HeLa) in a dose-dependent manner ( Fig. 1A ), which was consistent with previous studies that demonstrated that metformin significantly reduced the viability of thyroid cancer, osteosarcoma, leukemia and bile duct cancer cells by downregulating the expression of the antiapoptotic protein Bcl-2, and upregulating the expression of the proapoptotic proteins Bak and Bax ( 16 , 48 50 ). The present study also indicated that HeLa cells were more sensitive to metformin compared with CaSki and C33A cells, which may be caused by cell-type specificity and mutations in cancer-related genes resulting in resistance to the anti-proliferative effects of metformin.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study indicated that metformin significantly reduced human cervical cancer cell viability (CaSki, C33A and HeLa) in a dose-dependent manner ( Fig. 1A ), which was consistent with previous studies that demonstrated that metformin significantly reduced the viability of thyroid cancer, osteosarcoma, leukemia and bile duct cancer cells by downregulating the expression of the antiapoptotic protein Bcl-2, and upregulating the expression of the proapoptotic proteins Bak and Bax ( 16 , 48 50 ). The present study also indicated that HeLa cells were more sensitive to metformin compared with CaSki and C33A cells, which may be caused by cell-type specificity and mutations in cancer-related genes resulting in resistance to the anti-proliferative effects of metformin.…”
Section: Discussionsupporting
confidence: 93%
“…Apoptosis, also known as type I genetically programmed cell death, is a normal biological process described by stereotypical morphological alterations involving nuclear fragmentation and condensation, membrane blebbing, and apoptotic body formation [ 189 , 190 ]. Two significant apoptosis pathways have been reported: the mitochondria-mediated pathway and death receptor-mediated pathway, which depend on the caspase activation [ 191 ].…”
Section: Roles Of Ros Molecules In Pcamentioning
confidence: 99%
“…Briefly, doxorubicin is one of the main drugs used in chemotherapy; it promotes cell death by DNA damage, oxidative stress, and mitochondrial dysfunction [ 36 ]. On the other hand, metformin inhibits complex 1 of the electron transport chain in the mitochondria, activating AMPK and abrogating mTOR phosphorylation, leading to autophagy activation [ 37 ]. Together with this fact, metformin is considered a powerful hypoglycemic that reduces glucose blood levels, promoting a decrease in the metabolic rate [ 38 ].…”
Section: Discussionmentioning
confidence: 99%